Anti-herpes simplex virus type 2 of Drymaria diandra blume medicinal plant - Nikomtat J. (2014)
Anti-herpes simplex virus type 2 of dichloromethane and methanol extracts of Thai medicinal plant, Drymaria diandra Blume was investigated on Green Monkey Kidney cells. Cytotoxicity tests performed by the MTT assay revealed that 50% cytotoxicity dose of dichloromethane and methanol extracts were 90±2 and 631±32 μg/ml respectively. In all experiments, non-toxic concentrations of the plant extracts were used to test the inhibitory effect on various steps of herpes simplex virus type 2 (HSV-2) multiplication cycle. HSV-2 particles were directly inactivated by the extracts since 1 hour of treatment. HSV-2 infection was inhibited by the methanol extract with the 50% effective dose of 166.6±23.1 μg/ml. Moreover, both extracts inhibited HSV-2 attachment and penetration. The extracts also showed potent inhibitory activities against viral deoxyribonucleic acid synthesis as determined by real time polymerase chain reaction. Western blot analysis showed that HSV-2 proteins, particularly those at approximately 45 kDa were inhibited by the extracts after detection by horseradish peroxidase-conjugated immunoglobulin G against HSV. Therefore, this study demonstrated the inhibitory efficacy of Drymaria diandra Blume extracts against herpes simplex virus infection as a potential anti-HSV agent.